Exploring the meaningfulness of literacy programs among junior high school students: A phenomenological study - Zhia Malika; Sandi Putra (Jurnal Inovasi Guru Indonesia, 2026)
Background: Literacy programs have become central to educational reform initiatives aimed at strengthening students’ reading habits, critical thinking skills, and academic engagement. While numerous studies have evaluated the effectiveness of literacy movements in schools, limited research has explored how students themselves interpret and experience the meaningfulness of such programs. Understanding students’ lived experiences is essential for developing literacy initiatives that are both sustainable and contextually relevant. Objective: This study aimed to explore the meaningfulness of literacy programs among junior high school students through a phenomenological approach, focusing on how students interpret, internalize, and construct meaning from structured literacy activities in their school environment. Methods: This study employed a qualitative phenomenological design. Participants were 12 junior high school students who had actively participated in school literacy programs, including classroom reading corners and structured daily reading sessions. Data were collected through in-depth semi-structured interviews, non-participant observations, and document analysis. Data analysis followed phenomenological procedures, including identification of significant statements, thematic clustering, and development of composite textual and structural descriptions to capture the essence of students’ lived experiences. Results: The findings revealed five major themes: literacy as enjoyment, literacy as self-development, literacy as social interaction, literacy as academic support, and literacy as identity formation. Students perceived literacy programs as emotionally engaging, intellectually enriching, and socially meaningful. Accessible reading spaces, structured reading schedules, teacher facilitation, and multimodal resources were identified as key factors that strengthened students’ engagement and sustained reading habits.   Conclusion: Literacy programs in junior high schools function not only as instructional strategies but also as experiential spaces that shape students’ cognitive, social, and identity development. A phenomenological perspective provides deeper insight into how literacy initiatives become meaningful for students.